The Characterization of Oriza sativa Husk and Royal Ponciana pods Bricquettes - edi widodo; Mohammad Dani Iswanto; Prantasi Harmi Thahjanti; Rachmat Firdaus (Universitas Muhammadiyah Sidoarjo, 2020)
Rice mills produce abundant husk waste. The husks are used as a mixing material for bricks because they are flammable and have capability to form hot coals with high calor. This potential is used to develop the husks into briquettes. This study used rice husks (oriza sativa) and flamboyant pods (Royal ponciana) as the main ingredients for forming briquettes. This pods was chosen because had not optimally used. The composition of rice husk briquettes and flamboyant fruit skins made of 16.7%: 83.3%, 33.4%: 66.6%, 50%: 50%, 66.6%: 33.4%, 83.3 %: 16.7%. The briquettes formed were measured the calorific value, mass reduction using the TGA (Thermogravimetric analysis) thermal measurement method, and measured the values ​​of moisture, ash, volatile, and fixed carbon content. The results of the measurement of the lowest calorific value in rice husk briquettes were 83.3% with a value of 4,551 cal / gram, while the highest value was 5,945 cal / gram in rice husk briquettes percentage of 16.7%. The result of TGA measurement of the largest mass reduction was briquettes with a percentage of husk 83.3% having the highest mass reduction of 11.1 mg. The results of the measurement of water content obtained 7.04%, 24.70% volatile, 9.98% ash content, 58.28% fixed carbon